Trigeminal Herpes Zoster Transited to Ipsilateral Occipital Neuralgia - Keita Takizawa; Zhimin Yan; Jumi Nakata; Andrew Young; Junad Khan; Mythili Kalladka; Noboru Noma (Neurology International, 2022)
The pain of occipital neuralgia (ON) is thought to be secondary to trauma or injury to the occipital nerve at any point along the course of the nerve. ON may also be caused by an infectious process (herpes zoster) or compression of the nerve. The patient, in this case, presented to our clinic with complaints of occipital pain and rash and swelling of the right lower jaw. One week before presenting to our clinic, the patient developed severe pain in the first division of the trigeminal region with erythema and vesicles. A blood test showed a remarkably high antibody titer for varicella–zoster virus (VZV). The patient was prescribed oral valacyclovir (Valtrex®) (3000 mg/day), which resulted in the complete remission of the rash and blisters in the occipital region. This highlights the importance of considering neuroanatomy of the trigeminal region and cervical nerve.